Dermatology in COVID-19 pandemic: a review of manifestation, prevention, and treatment of personal protective equipment adverse skin reactions - I Gusti Ayu Nitya Indira; I Made Sutha Saskara (DiscoverSys Inc, 2020)
Since declared as a global pandemic by World Health Organizations on 11th March 2020, per early July 2020, COVID-19 total confirmed cases count had surpassed 11 million cases. COVID-19 poses a new challenge to healthcare workers with a new standard of care and managing COVID-19 patients. Healthcare workers must adhere to stricter hand hygiene, and the new Personal Protective Equipment (PPE) protocol brings forth new problems for healthcare workers. Skin problems have become the most common and preventable adverse effects of the daily and prolonged use of PPE. This could inadvertently cause protocol breaches, such as mask touching, scratching, or off-protocol PPE adjustment. Damage in the skin could also cause discomfort, and skin exposure may serve as a new port of entry for a secondary infection. In this study, we review various studies regarding the adverse effects, prevention, and therapy of the skin problems related to COVID-19 PPE use.